Errata - anonymous (Management Science, 1968)
Errata to the article Charnes A., W. W. Cooper, J. K. Devoe, D. B. Learner, W. Reinecke. 1968. A goal programming model for media planning. Management Sci. 14(8, April) B-423–B-430.